Özel Sigorta Hukukunda Rizikonun Dağıtılması İlkesi - Omağ, Merih Kemal (İstanbul Kültür Üniversitesi, 2002)
Sigortanın esası, zararın sigortalılar topluluğuna dağıtılmasıdır. İç dağıtımda sigortacı rizikoyu aynı tehlikeye maruz sigortalılar topluluğu arasında paylaştırır ve dağıtır. Dış dağıtımda ise sigortacı, taşıdığı rizikoyu kendisinin dışındaki sigorta kuruluşlarına dağıtır ve paylaştırır. Dış dağıtıma işlerlik kazandıran üç teknik müessese şunlardır: Müşterek sigorta, mükerrer sigorta, retrosesyondur. Müşterek sigorta, da ise; sigortacı belirli oranda rizikoları üzerinde tutar geri kalanını reasüröre tekarar sigortalar. Reasüröre tekrar sigortalar. Reasürans, sigortacının ödeme gücünü takviye eder. Retrosesyon ise; reasürörün taşıdığı rizikonun bir kısmını başka bir sigortacıya devretmesi işlemidir.

The basis of insurance is the distribution of the damage amangst an insured group. In international distribution, the insurer distributes and divides the risk amangst the insureds facing the same dangers. In external distribution, the insurer distributes and divides the risk, amangst the other insurance companies. External distribution has three main technical structures: Coinsurance, reinsurance and retrocession. Coinsurance is the distribution of the risk amongst various insurers. In the frame of such insurance, each insurer guarantees a definite part of the risk. Coninsurance covers high amounted risk. In reinsurance the insurer keep a definite part of the risk on himself and reinsurens the rest by the means of other insurers. Reinsurance strengths the capability of the insurer in payment. Retrocession is an operation which the reinsurer assign a part of the reinsured risk to another insurer.
Keywords: Özel sigorta; Özel sigorta riziko